Acne in late adolescence is not associated with a raised risk of subsequent malignant melanoma among men. (December 2017) - Mota Garcia, Teresa; Hiyoshi, Ayako; Udumyan, Ruzan; Sjöqvist, Hugo; Fall, Katja; Montgomery, Scott
Highlights: The association of acne with malignant melanoma (MM) in men is unclear. This study followed over 240, 000 men in Sweden from adolescence to middle age. Acne was not associated with subsequent MM. Abstract: Background: To evaluate the association of acne in late adolescence with the risk for subsequent malignant melanoma (MM) in men. Methods: Swedish register-based cohort study of 242, 096 males born between 1952 and 1956, who took part in compulsory assessments for Swedish military conscription in late adolescence between 1969 and 1975, with subsequent diagnoses of MM (n = 1, 058) up to December 31, 2009. Covariates included measures of childhood circumstances and information from adolescence on presence of acne, physical fitness, cognitive function, body mass index (BMI), and a summary of diagnoses. Cox regression was used for the analysis. Results: In total 1, 058 men were diagnosed with MM. Acne was not associated with subsequent MM, with an adjusted hazard ratio (and 95% confidence interval) of 0.95 (0.61 to 1.49). Men with parents who were agricultural workers, and men who lived in northern Sweden, had lower physical fitness, or lower cognitive function had a lower risk of MM. Overweight and obesity was associated with a raised risk, with an adjusted hazard ratio of 1.39 (1.14, 1.71). Conclusions: Acne in late adolescence is unlikely to represent a raised risk for subsequent MM in men. Overweight or obesity was identified as a raised risk for MM, possibly due to the associated increased skin surface area.